Open globe injury in Hospital Serdang - an 8-year retrospective review - Omar, Nazri; Abdul Muna'aim, Maimunah; Ismail, Rozita; Md. Saleh, Rafidah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2017)
Introduction: Open globe injury may lead to devastating visual outcome. Urgent management and subsequent follow-up is important to maximise recovery. More data on open globe injury in Malaysia is needed to identify risk groups and prognostic factors. This study was carried out to investigate open globe injury, the socio-epidemic profile, clinical characteristics and outcome of the open globe injury in the Hospital Serdang, Malaysia. Methods: All patients managed for open globe injury to Hospital Serdang from January 2006 to December 2013 were included in this retrospective case review. Student’s T-test was used to determine difference between means and chi-square for categorical data. P value of less than 0.05 was regarded as statistically significant. Results: There were 155 patients managed for open globe injury with three of them had bilateral involvement. As such, there were 158 cases eligible for analysis in this study. The average age was 32.2 ± 16.5 years (mean ± standard deviation, SD). Male was at higher risk for open globe injury. Predictors for poor visual outcome were foreign nationality (p=0.047), lid laceration (0.008), type of injury (p=0.001), site of injury (p=0.008), RAPD (p<0.001), uveal prolapse (p<0.001), hyphaema (p=0.008), lens damage (p=0.010), vitreous loss (0.014), retinal detachment (p=0.011), intraocular foreign body (IOFB) (0.014) and poor presenting uncorrected visual acuity (UCVA) (p<0.001). Conclusions: Occupational injury was a main cause of open globe injury in Hospital Serdang. Although in general the visual outcome is good, effort should be put to prevent work-related injury.